Perceptions of Ilonggo print journalists of the role of the Office of the Ombudsman in the investigation of graft and corruption in public services - Gapulan, Evan John B.
The study describes the differences of perceptions among the Ilonggo print journalist of the Office of the Ombudsman and on its role in investigating graft and corruption in government. The study was conducted in Iloilo City. Thirteen journalists from theree major daily newspapers, namely: Daily Headlines, Panay News, and Sun Star Daily participated as respondents of the study. An ope-ended questionnaire was used to gather the perceptions of the journalists. The responseswere analyzed and categorized as positive or negative perceptions. The results of the study show varied levels of perception among the Ilonggo print journalists of the Office of the Ombudsman and in relation to its role in the investigation of graft and corruption in public service or the bureaucracy. The study concludes that the Ilonggo print journalists lack knowledge of the mandate, function, powers and roles of the Office of the Ombudsman, but they fully acknowledge and recognize it. The negative perceptions of the Ilonggo journalists on many aspects pertaining to the Office of the Ombudsman can be attributed to their desire for output, more accomplishments, and better performance from this Constitutionally mandated anti-graft body. The researcher recommends that further research should be conducted with the topic under study using in-depth interviews for a more valid and reliable analysis of perceptions.